Homo‐Tandem Polymer Solar Cells with VOC >1.8 V for Efficient PV‐Driven Water Splitting. Issue 17 (4th March 2016) - Gao, Yangqin; Le Corre, Vincent M.; Gaïtis, Alexandre; Neophytou, Marios; Hamid, Mahmoud Abdul; Takanabe, Kazuhiro; Beaujuge, Pierre M.
Abstract : Efficient homo‐tandem and triple‐junction polymer solar cells are constructed by stacking identical subcells composed of the wide‐bandgap polymer PBDTTPD, achieving power conversion efficiencies >8% paralleled by open‐circuit voltages >1.8 V. The high‐voltage homo‐tandem is used to demonstrate PV‐driven electrochemical water splitting with an estimated solar‐to‐hydrogen conversion efficiency of ≈6%.